Children's entertainment television in India: The changing scenario and the Indian child. Issue 3 (1st November 2018) - Das, Shukla; Kini, Saesha (Sashank)
Indian children's commercial television started in 1995 with foreign channels and gathered momentum in the early 2000s. After 2008, the spurt in home-grown programming added an indigenous dimension. However, the home-grown programmes fall short in numbers as compared to their foreign counterparts and are plagued with various issues such as lack of diversity in genres, inadequate educational programming, regressive character portrayals, stereotypical gender representation and underrepresentation of the India's cultural treasure trove. This article reviews the shortfall of home-grown children's programming. It then examines the genres, themes, characters, age segmentation, gender balance and cultural inclusiveness on Indian children's television and suggests how the programming can improve in quality and create an original, relevant and contemporary world on television for the Indian child.